The uncertainty trope: the duty to treat during a pandemic. (April 2021) - Zubaran, Carlos; Freeman, Alexander
Background: Past guidance in the codes of practice urged doctors to provide treatment even in the context of extreme adversities. Despite the significant societal changes of recent times, contemporary guidance regarding the duty to treat during a pandemic has been limited. Objective: The authors herewith examine deontological aspects pertaining to the duty to treat during a pandemic and the potential disruptions to health care services. Conclusion: The ethical, legal and professional guidance for duty of care during a pandemic is uncertain and demands further debate.